ACUTE ENTERIC INFECTIONS POLYMERASE CHAIN REACTION ASSAY IN PEDIATRIC PRACTICE: OPPORTUNITIES AND CHALLENGES - E. D. Sokolova; A. M. Galtaeva; O. U. Zamurei; O. V. Didichenko; U. V. Sokolova; V. A. Muratova; O. U. Ligorova; I. N. Zhuravleva; M. A. Makarova; L. A. Kaftyreva (Инфекция и иммунитет, 2016)
The aim of the study is estimate the opportunities of local multi-prime PCR reagents kits in children enteric infections etiological diagnostics amongst the patients with diarrhoea vs traditional bacteriological methods. We used 4 kits of reagents that provide multiple pathogens simultaneous indication in one sample: 1) Rotavirus, Norovirus, Astrovirus; 2) Shigella spp./EIEC, Salmonella spp., Campylobacter spp.; 3) Yersinia enterocolitica and Yersinia pseudotuberculosis; 4) E. coli: EIEC (enteroinvasive), EPEC (enteropathogenic), ETEC (enterotoxigenic), EHEC (enterohaemorrhagic), EAgEC (enteroaggregative). It has been shown that the viral intestinal infections is increased by 14%, bacterial — in 2,5 times. PCR diagnostics identified in 62% of patients the viral gastroenteritis: Rotavirus (52%), Norovirus (9%), Astrovirus (1%). Detected bacterial pathogens PCR markers number proved up to 2.5 times high than according to bacteriological examination. The spectrum of bacterial agents increased due to E. coli and Y. enterocolitica. PCR diagnostics increased detection of Campylobacter up to 2 times. Detected E. coli DNA prevalence: EPEC — 66%, EAgEC, ETEC and EHEC were 31%, 9% and 4%, respectively. DNA Campylobacter spp. and E. coli constituted 2/3 of all findings: Campylobacter spp. (41%), E. coli (24%), Salmonella spp. (19%), Yersinia spp. (11%), Shigella spp./EIEC (5%). The positive results of bacteriological and serological methods duplicate the positive results of PCR diagnostics. In general, the positive results of PCR diagnosis of bacterial pathogens were detected in 46.35% of the examined patients. In 48.4% of patients identified PCR markers viral — bacterial infection, in 5.25% — of bacterial associations, in 11% of them were found the DNA 2–3 bacterial pathogens. The study was shown in children in St. Petersburg in 2012–2014 dominated rotavirus infection, campylobacteriosis and escherichiosis. The prevalence of viral-bacterial confections is more than 50% of all diagnosed cases.